Racial and ethnic disparities in a state‐wide registry of patients with pancreatic cancer and an exploratory investigation of cancer cachexia as a contributor to observed inequities. (9th May 2019) - Permuth, Jennifer B.; Clark Daly, Ashley; Jeong, Daniel; Choi, Jung W.; Cameron, Miles E.; Chen, Dung‐Tsa; Teer, Jamie K.; Barnett, Tracey E.; Li, Jiannong; Powers, Benjamin D.; Kumar, Nagalakshmi B.; George, Thomas J.; et al.
Abstract: Pancreatic cancer (PC) is characterized by racial/ethnic disparities and the debilitating muscle‐wasting condition, cancer cachexia. Florida ranks second in the number of PC deaths and has a large and understudied minority population. We examined the primary hypothesis that PC incidence and mortality rates may be highest among Black Floridians and the secondary hypothesis that biological correlates of cancer cachexia may underlie disparities. PC incidence and mortality rates were estimated by race/ethnicity, gender, and county using publicly available state‐wide cancer registry data that included approximately 2700 Black, 25 200 Non‐Hispanic White (NHW), and 3300 Hispanic/Latino (H/L) Floridians diagnosed between 2004 and 2014. Blacks within Florida experienced a significantly ( P  < 0.05) higher incidence (12.5/100 000) and mortality (10.97/100 000) compared to NHW (incidence = 11.2/100 000; mortality = 10.3/100 000) and H/L (incidence = 9.6/100 000; mortality = 8.7/100 000), especially in rural counties. To investigate radiologic and blood‐based correlates of cachexia, we leveraged data from a subset of patients evaluated at two geographically distinct Florida Cancer Centers. In Blacks compared to NHW matched on stage, markers of PC‐induced cachexia were more frequent and included greater decreases in core musculature compared to corresponding healthy control patients (25.0% vs 10.1% lower), greater decreases in psoas musculature over time (10.5% vs 4.8% loss), lower baseline serum albumin levels (3.8 vs 4.0 gm/dL), and higher platelet counts (332.8 vs 268.7 k/UL). Together, these findings suggest for the first time that PC and cachexia may affect Blacks disproportionately. Given its nearly universal contribution to illness and PC‐related deaths, the early diagnosis and treatment of cachexia may represent an avenue to improve health equity, quality of life, and survival. Abstract : Here we report the first analysis to illustrate the disproportionate pancreatic cancer burden among Blacks in Florida's racially/ethnically diverse population and the first analysis of cancer cachexia as a possible biological contributor to observed disparities. Cancer cachexia is measurable and targetable, and our exploratory analysis suggests timely diagnosis and treatment of cachexia may reduce disparities, increase quality of life, and improve survival.